Detecting the Non-physiological, Surgically Tailored Ileocolic Anastomosis Using the Wireless Motility Capsule. A Pre- and Post-operative, Prospective, Within Subject Trial - Thorsen, Yngve (J Neurogastroenterol Motil, 2017)
BACKGROUND/AIMS: Wireless motility capsule (WMC) detects the ileocolic junction (ICJ) in most non-operated patients. We find no data concerning this examination in patients where the ileocolic valve is replaced by a per definition incompetent, surgically created ICJ. We wanted to see if WMC could detect the ICJ after a right colectomy and assess the competency. METHODS: Prospective cohort study using a within-subject design to eliminate subject-subject variability. Selected patients operated with right colectomy underwent 3 WMC examinations (pre-operatively, 3 weeks, and 6 months after surgery). RESULTS: Twenty patients (8 men) included, 7 (4 men) excluded due to poor recordings (4) and unforeseen events (3). Thirteen patients (4 men), median age 63 years completed 3 tests. Median bowel lengths removed were 11 cm for ileum and 21 cm for colon. Thirty-nine examinations analyzed by 2 physicians who found all 13 ICJs at 3 examinations with high inter-rater reliability (intra-class correlation coefficient: 0.99, 0.91, and 0.99 respectively), whereas the computer found 9, 8, and 10 out of the 13 ICJs, respectively. Computed values significantly more often deviated from the 2 raters. Mean magnitude and duration of pH-drop at the ICJ (3 examinations) was 1.16–1.02–1.13 pH units and 3.15–4.78–3.75 minutes, respectively. pH-drop was smaller and duration longer at 3 weeks. We found no differences between the pre-operative (competent ICJ) and post-operative 6-month examinations (incompetent ICJ). Highest pressure immediately prior to ICJ was equal before and after surgery. CONCLUSION: WMC can identify the non-physiological ICJ after right colectomy. Ileocolic competence cannot be assessed.